When is upstream collusion profitable?. (1st April 2019) - Gu, Dingwei; Yao, Zhiyong; Zhou, Wen; Bai, Rangrang
Abstract: Motivated by the recent antitrust cases in which Japanese auto parts suppliers colluded to raise supply prices against their long‐term collaborators, the Japanese carmakers, we study the conditions under which an upstream collusion is profitable even after compensating downstream direct purchasers. Oligopoly competition in successive industries is shown to give rise to a vertical externality and a horizontal externality. If a collusive price of intermediate goods better balances the two externalities, the collusion will raise the joint profit of all firms in the two industries and is therefore profitable for the upstream after compensation of downstream firms.